Outcomes of mucosal melanoma of the head and neck. Issue 2 (23rd November 2015) - Frakes, Jessica M; Strom, Tobin J; Naghavi, Arash O; Trotti, Andy; Rao, Nikhil G; McCaffrey, Judith C; Otto, Kristen J; Padhya, Tapan; Caudell, Jimmy J
Abstract: Introduction: Mucosal melanoma of the head and neck is a rare disease with limited data available on outcomes; therefore, we reviewed our institutional experience. Methods: An institutional database was queried and 38 patients with head and neck mucosal melanoma were identified. Charts were abstracted and local control (LC), progression‐free survival (PFS) and overall survival (OS) were calculated. Results: Most patients had T4 disease (86%), although nodes were positive in 11%. En bloc or endoscopic resection was performed on 93%. Adjuvant or definitive radiotherapy to a median dose of 60 Gy was utilized in 90%. Chemotherapy was given in 21%, and 16% received interferon. Three‐year LC, PFS and OS were 90%, 48% and 59%, respectively. Median OS was 4.6 years. Site of first failure was distant in 52% of cases. Conclusion: With aggressive therapy median OS was 4.6 years in this cohort. Distant recurrence remains the primary mode of failure. It may be reasonable to include mucosal melanoma patients in trials of systemic agents along with high‐risk cutaneous melanomas.